Perancangan Video Edukasi Waspada Child Grooming Bagi Para Remaja - Sagita Salsabilla; Ahmad Khoirul Anwar; Arif Yulianto (Universitas Sahid Surakarta, 2026)
Abstract The increasing development of technology and the internet provides many benefits and conveniences for society, especially for teenagers. However, increased access to technology and the internet is a second factor in vulnerability to electronic-based sexual violence, such as child grooming. The results of the ECPAT report in 2023 showed that there were 16 cases from the previous 29 cases in 2022. The number of cases experienced a decrease but in terms of electronic-based sexual violence cases were relatively high, one of which was grooming for sexual purposes. The increase in child grooming cases is based on adolescents' lack of understanding and low reporting, making them vulnerable to child grooming. Victims of child grooming should have the courage to speak up. However, in reality, many victims dare not speak up due to negative stigma from society. Based on these problems, the design of an educational video for teenagers to be aware of child grooming is expected to be appropriate, engaging, and easy to understand, so that teenagers can avoid it. The goal of this design is to create an educational video discussing the signs of child grooming so that teenagers can avoid child grooming and prevent the creation of negative stigma in their surroundings, so that victims have the courage to speak up. This design uses video to deliver education and information in an easy-to-understand way for teenagers. Video is chosen because it conveys messages visually, making it easy for teenagers to understand and accessible via mobile devices. This design method uses the design thinking method, which consists of five stages: empathize, define, ideate, prototype, and test. The resulting design presents an effective educational video titled